Experimental determination of the coefficient of viscosity of the dry snow - R. A. Chernov (Лëд и снег)
Snow compaction is a natural process in the evolution of any snow cover, and this obviously changes the physical and mechanical properties of a snow thickness. The quantitative estimate of this process is acoefficient of the snow viscosity, which is linearly related to the rate of the snow cover deformation The technique for preparation and testing of samples with the fine-grain snow under condition of uniaxialcompression at negative temperatures is described. It was determined that values of the snow viscosity coefficient fall within the range from 0.10 to 0.30 g/cm³ for three temperature intervals. The viscositycoefficient of the fine-grain snow varies from 10⁸ до 10¹⁰ Па. The data obtained made possible to find the limits of variability of this coefficient for winter conditions on the Russian plain. A dependence of theviscosity coefficient on the snow density and temperature is proposed, and it describes the series of the above shown experimental data. It is shown that influence of changes in the viscosity coefficient of fine-grain snow on the snow properties depending on its density are comparable in scale to the influence of the temperature. The result may be useful for modeling the evolution of snow cover.